2020
DOI: 10.1002/ppp3.10158
|View full text |Cite
|
Sign up to set email alerts
|

Understanding photothermal interactions will help expand production range and increase genetic diversity of lentil (Lens culinarisMedik.)

Abstract: Lentil is a staple in many diets around the world and growing in popularity as a quick‐cooking, nutritious, plant‐based source of protein in the human diet. Lentil varieties are usually grown close to where they were bred. Future climate change scenarios will result in increased temperatures and shifts in lentil crop production areas, necessitating expanded breeding efforts. We show how we can use a daylength and temperature model to identify varieties most likely to succeed in these new environments, expand g… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
66
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

6
3

Authors

Journals

citations
Cited by 33 publications
(70 citation statements)
references
References 56 publications
4
66
0
Order By: Relevance
“…The physiological similarity between ILL 2601 and the Medicago mutants described above strengthens the idea that the FTa1 - FTa2 intergenic deletion might be the causal polymorphism for the observed FTa1 upregulation. In view of its potential significance, we designed a PCR-based specific marker for this polymorphism (Supplementary Table 10, Supplementary Figure 8), and examined its prevalence in a lentil collection of 48 accessions available at the University of Tasmania and across a broader diversity panel of 324 accessions (Wright et al 2021), both selected to cover a wide range of geographic origins. Results from the screening were similar in both collections and show that, globally, the deletion is common within lentil germplasm and 23-37.5% of all accessions carry the deletion ( Supplementary Figure 9, Supplementary Figure 10 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The physiological similarity between ILL 2601 and the Medicago mutants described above strengthens the idea that the FTa1 - FTa2 intergenic deletion might be the causal polymorphism for the observed FTa1 upregulation. In view of its potential significance, we designed a PCR-based specific marker for this polymorphism (Supplementary Table 10, Supplementary Figure 8), and examined its prevalence in a lentil collection of 48 accessions available at the University of Tasmania and across a broader diversity panel of 324 accessions (Wright et al 2021), both selected to cover a wide range of geographic origins. Results from the screening were similar in both collections and show that, globally, the deletion is common within lentil germplasm and 23-37.5% of all accessions carry the deletion ( Supplementary Figure 9, Supplementary Figure 10 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, its subsequent spread south to the Indian subcontinent and Ethiopia, and north to the Caucasus and beyond, likely depended on significant phenological changes suited to different seasonal climates and cropping patterns. Some insight into this variation was provided by physiological studies which distinguished independent influences of photoperiod and temperature across diverse lentil accessions and described flowering behaviour with a simple photo-thermal model (Summerfield et al 1985;Erskine et al 1990;Wright et al 2021). These studies also observed variation in relative responsiveness to photoperiod and temperature, as well as in time-to-flower under the most inductive conditions, identifying several lines showing minimal acceleration of flowering with increases to temperature, and several others relatively unresponsive to photoperiod (Erskine et al 1990).…”
Section: Introductionmentioning
confidence: 99%
“…ILL 1704 is a landrace from Ethiopia with moderate resistance to ascochyta blight (Tullu et al, 2010). The GWAS panel was a subset of 200 lentil genotypes selected from the Lentil Diversity Panel (LDP; N=324) (Haile et al, 2020; Wright et al, 2021; http://knowpulse.usask.ca/Lentil-Diversity-Panel). The LDP consists of 324 accessions assembled from the gene banks of Plant Gene Resources of Canada (PGRC), the USDA, the International Center for Agricultural Research in the Dry Areas (ICARDA), and includes cultivars developed at the Crop Development Centre (CDC), University of Saskatchewan (USask).…”
Section: Methodsmentioning
confidence: 99%
“…Real-world datasets consist of data generated by the University of Saskatchewan Pulse Crop research group with a focus on the AGILE Genome Canada grant. Specifically, genotypic data consist primarily of the L. culinaris exome capture assay ( 22 ) and phenotypic data consist primarily of the L. culinaris AGILE diversity panel with a focus on phenology traits ( 24 ). The genotypic dataset consists of 105 340 269 data points across 534 individuals and 372 506 variants.…”
Section: System and Methodsmentioning
confidence: 99%